2005
DOI: 10.1055/s-2004-813903
|View full text |Cite
|
Sign up to set email alerts
|

Charakterisierung eines experimentellen venösen Thrombosemodells mittels MRT, Phlebographie und Histologie

Abstract: The thrombus model closely resembles the human venous stagnation thrombus of different organizational stages. With state-of-the-art MRI techniques, thrombi were only partially displayed with the visibility depending on thrombus age. The model may be suitable for evaluating new and potentially more effective MRI techniques for improved thrombus visualization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
4
1
1
Order By: Relevance
“…To our knowledge, venous thrombus models in previous in vivo studies have been induced with thrombin injection or electric stimulation [16][17][18] and have shown signal patterns that are different from our study. It is possible that the thrombi observed in those studies have mainly consisted of platelets and fibrins [22].…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…To our knowledge, venous thrombus models in previous in vivo studies have been induced with thrombin injection or electric stimulation [16][17][18] and have shown signal patterns that are different from our study. It is possible that the thrombi observed in those studies have mainly consisted of platelets and fibrins [22].…”
Section: Discussioncontrasting
confidence: 78%
“…Stasis seems to play the most important role in thrombus formation based on the physiological and anatomical venous character [15]. In vivo studies with animal models of venous thrombosis using MRI have already been reported [16][17][18]. In those studies, venous thrombi were induced by thrombin injection or by electric stimulation to the vessel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-quantitative comparison of the MR images to immunohistochemical staining of the same thrombus (Fig. 2d-g) show that bright regions in MR images correspond to laminations of coalescent platelets mixed with fibrin meshwork, known as Zahn lines (10,11,18,19). Such bright patterns in T 1 -weighted MR images, as in the example in Figure 2, were found in 18 of 21 samples.…”
Section: Resultsmentioning
confidence: 76%
“…Eine große klinische Studie in der RöFo hat des Weiteren gezeigt, dass die MRT bei der Erkennung von linksventrikulären Thromben der Echokardiographie überlegen ist. Optimierungen von Sequenzen zur Thrombusdetektion lassen sich von weiteren Analysen, basierend auf einem kürzlich vorgestellten Tiermodell venöser Thromben, erwarten [59]. Eine klinisch wichtige Erkenntnis zu Patienten mit linksatrialen Thromben brachte eine weitere große klinische Studie zutage, die zeigte, dass stumme zerebrale Embolien viel häufiger sind als bisher gedacht und sogar unter effektiver Antikoagulation auftreten können [60].…”
Section: Mrtunclassified